(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the methodology of philological research and its modern approaches in the context of contemporary scientific development. It analyzes how traditional methods of linguistic and literary studies have evolved into interdisciplinary and technology-based frameworks, including corpus linguistics, cognitive linguistics, discourse analysis, and computational approaches. The study highlights the importance of integrating classical philological traditions with modern innovations to enhance both theoretical and practical outcomes.